2022
DOI: 10.1186/s12865-022-00488-2
|View full text |Cite
|
Sign up to set email alerts
|

Exhausted phenotype of circulating CD8+ T cell subsets in hepatitis B virus carriers

Abstract: Background Chronic hepatitis B virus (HBV) infection is characterized by the presence of dysfunctional exhausted CD8+ T cells that hamper viral control. We investigated the phenotypic heterogeneity of exhausted CD8+ T cells in HBV carriers. Methods We enrolled 31 HBV carriers and 23 healthy controls (HCs) in our study. Peripheral blood mononuclear cells (PBMCs) were isolated, and flow cytometry was used to determine the phenotypic distribution of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…All included patients were chronically infected with HBV. The exclusion criteria of the included studies were similar, as most studies excluded patients coinfected with other hepatitis viruses and/or human immunodeficiency virus (HIV) [ 11 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 ], with concurrent liver disease [ 16 , 21 , 22 , 23 , 24 , 26 , 29 , 30 ], and/or patients receiving antiviral or immunomodulatory therapy [ 11 , 15 , 16 , 17 , 21 , 23 , 24 , 28 , 30 ]. One study did not provide detailed information on patients’ inclusion or exclusion criteria [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included patients were chronically infected with HBV. The exclusion criteria of the included studies were similar, as most studies excluded patients coinfected with other hepatitis viruses and/or human immunodeficiency virus (HIV) [ 11 , 17 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 29 , 30 , 31 ], with concurrent liver disease [ 16 , 21 , 22 , 23 , 24 , 26 , 29 , 30 ], and/or patients receiving antiviral or immunomodulatory therapy [ 11 , 15 , 16 , 17 , 21 , 23 , 24 , 28 , 30 ]. One study did not provide detailed information on patients’ inclusion or exclusion criteria [ 9 ].…”
Section: Resultsmentioning
confidence: 99%
“…Jiang et al [ 22 ] investigated the phenotypic heterogeneity of exhausted CD8 + T cells in the peripheral blood of 31 CHB patients and 23 healthy controls. Compared to healthy controls, CD8 + T cells in CHB patients had higher expression levels of the inhibitory receptors lymphocyte-activation gene 3 (LAG3) and T cell immunoglobulin and mucin domain-containing protein 3 (TIM3).…”
Section: Resultsmentioning
confidence: 99%
“…Further studies showed that these CD8 + T-cells produced lower levels of IFNγ, tumour necrosis factor α, and granulozyme B. 43 tinctly promoted the production of antibodies by B-cells. 44 In addition, several studies have found that the high frequency of CXCR5 + CD8 + T-cells was associated with a lower HBV DNA load and decreased HBsAg concentration and was negatively correlated with ALT level.…”
Section: Re S E Arch Prog Re Ss On C Xcr+ Cd8 + T Cell S In Hbv Infec...mentioning
confidence: 97%
“…Studies have shown that the levels of inhibitory receptors (such as TIM3 and PD‐1) on the surface of CD8 + T cells in HBV carriers are higher than those in healthy controls. Further studies showed that these CD8 + T‐cells produced lower levels of IFN‐γ, tumour necrosis factor α, and granulozyme B 43 . CXCR5 + CD8 + T‐cells in the peripheral blood of CHB patients and HBV‐related hepatocellular carcinoma (HCC) patients were significantly up‐regulated compared to healthy individuals.…”
Section: Research Progress On Cxcr5+cd8+ T Cells In Hbv Infectionmentioning
confidence: 99%
“…CD8+ T cells are essential IFN γ-mediated non-cytopathic mechanisms to clear HBV. However, in chronic HBV infection, CD8+ T cells are very few and appear to be exhausted, resulting in an obstruction of viral control ( Jiang et al., 2022 ). Exhausted CD8+ T cells achieve metabolic recombination for glycolysis by increasing GLUT1 expression, thereby rapidly providing energy and metabolites to support proliferation and effector T-cell metabolic changes to meet antiviral requirements, although glycolysis is less energy efficient than the TCA cycle ( Schurich et al., 2016 ), and hence interference with glycolysis may lead to T lymphocyte dysfunction ( Zhou X. et al., 2021 ).…”
Section: Hepatitis B Virusmentioning
confidence: 99%